US immigration policy at a crossroads - Harriet Orcutt Duleep (Institute for the Study of Labor (IZA), 2013)
Two issues have taken center stage in the recent debates about U.S. immigration policy: one, illegal immigration and more generally the entrance of poorly educated individuals into the U.S. economy and two, whether the U.S. should continue its family-based admissions system or move towards a skills-based system. This paper analyzes these issues culling evidence from the history of U.S. immigration policy, the experiences of different types of U.S. immigrants, and cross-national comparisons.
Keywords: J15; J24; J39; J61; L26; 330; immigration; illegal immigration; effect on poorly educated natives; entrepreneurship; human capital investment; skill transferability; opportunity cost; learning transferability; family-based admissions; permanence; Migrationspolitik; Einwanderungsrecht; Qualifikation; Familie; Illegale Einwanderung; USA